Generation of high-titer of neutralizing polyclonal antibodies against heat-stable enterotoxin (STa) of enterotoxigenic Escherichia coli - Aref, Nasr-Eldin M. (2012)
In this study, polyclonal antibodies with high titer and avidity to native heat-stable enterotoxin (STa) of enterotoxigenic Escherichia coli (ETEC) have been generated and evaluated for their neutralizing effect in STa-induced enterotoxic animal model. Native STa was purified to homogeneity and coupled to modified bovine serum albumin (MBSA) using dimethylformamide (DMF)-based conjugation protocol. STa conjugate was used for immunization of female New Zealand white rabbits. The humoral immune response of the rabbits against native STa was monitored and evaluated for its antibody binding and neutralization capacity by ELISA and suckling mouse assay, respectively. After three subsequent boosts by STa conjugate, the animals were capable of eliciting high levels of STa-antibody binding titer (10(6)) and STa-neutralizing antibody capacity (3 × 10(4) mouse units of STa/ml serum). STa antibody maturation (avidity) was improved dramatically after multiple boosters with the STa conjugate. Comparison of the avidity of STa antibodies demonstrated that the strength in the STa antibody avidity developed in time corresponding to the development of the STa-neutralizing and binding titers. High avid STa antibodies (48.21% avidity index) were demonstrated 24 weeks post immunization (PI). However, differences in the onset of STa antibody production were noticed among animals and may need further investigation.